2023
DOI: 10.3390/jcm12020638
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Related Osteonecrosis of the Jaw: A Cross-Sectional Survey among Urologists in Switzerland, Germany, and Austria

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) is a potentially preventable adverse side effect of mainly antiresorptive drugs. MRONJ is expected to become a growing clinical problem due to the aging population and the increasing number of patients requiring antiresorptive agents. Knowledge and awareness about MRONJ and elimination of the oral and dental risk factors before starting antiresorptive therapy (AR) are fundamental to reducing the incidence of MRONJ. In urology, ARs are used primarily in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…While several previous reports highlighted that a low proportion of prescribers still do not routinely refer their patients to dentists before initiating AR therapy (Taguchi et al, 2016), a recent survey surprisingly showed that 90% of a sample of urologists from Austria and Germany declare they implemented referrals to dentists for oral examination before initiating AR (Calderaro et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…While several previous reports highlighted that a low proportion of prescribers still do not routinely refer their patients to dentists before initiating AR therapy (Taguchi et al, 2016), a recent survey surprisingly showed that 90% of a sample of urologists from Austria and Germany declare they implemented referrals to dentists for oral examination before initiating AR (Calderaro et al, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…In our survey the question about prostate cancer did not distinguish between BMAs at high doses and with monthly administration (as usual in metastatic castration-resistant disease) or BMAs at low doses and/or with delayed administration (recommended for hormone-sensitive metastatic cancer, as well as for prevention or treatment of cancer treatment-induced bone loss (CTIBL)). This issue should be further investigated in a more specific survey involving both urologists and oncologists, as well as specialists treating CTIBL [ 13 , 17 , 20 , 25 , 28 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines and recommendations show some heterogeneity and uncertainty about the choice of treatment drug (bisphosphonates versus denosumab), optimal treatment duration (one versus 2 years or indefinite treatment), de-escalation and delayed dosing schedules (e.g., zoledronic acid every 3 months instead of monthly administration) [ 3 5 , 8 , 10 ], as well as the management of side effects, such as MRONJ and hypocalcemia [ 6 – 9 , 11 ]. According to recent surveys and studies conducted in Europe and North America, the attitudes of prescribing physicians, as well as patients’ preferences and real-life practice patterns, are not fully homogeneous [ 12 28 ].…”
Section: Introductionmentioning
confidence: 99%